Claspin – checkpoint adaptor and DNA replication factor. (29th June 2018) - Smits, Veronique A. J.; Cabrera, Elisa; Freire, Raimundo; Gillespie, David A.
Abstract : Claspin was discovered as a Chk1‐interacting protein necessary for Chk1 phosphorylation and activation by the upstream kinase, ATR, in response to DNA synthesis inhibition in Xenopus oocyte extracts. Subsequent investigations have defined a molecular model in which Claspin acts as an adaptor or scaffold protein to facilitate activation of Chk1 by ATR within a multiprotein complex that forms on single‐stranded DNA at stalled replication forks and sites of DNA damage. Interestingly, Claspin is an unstable protein whose degradation via the proteasome is tightly regulated via ubiquitination and controlled by multiple ubiquitin ligases and deubiquitinases. As a result, Claspin levels fluctuate during the cell cycle, contributing to the regulation of checkpoint proficiency and playing a key role in terminating checkpoint‐mediated cell cycle arrest. In addition to its role in signalling genotoxic stress, Claspin is required to maintain normal rates of replication fork progression during unperturbed DNA replication and may contribute to the regulation of replication origin firing. Consistent with this, Claspin can bind directly to DNA, with particular affinity for branched or forked molecules, and it interacts with multiple protein components of the replisome. As expected for a protein with key roles in checkpoint signalling and genome duplication, aberrations of Claspin expression and structure have been observed in cancer. Claspin is furthermore targeted to facilitate viral replication and plays a role in suppressing cellular DNA synthesis in response to nongenotoxic endoplasmic reticulum stress. Here, we review the functions and regulation of Claspin with a focus on areas of active research. Abstract : Claspin is an adaptor molecule that facilitates activation of the checkpoint effector kinase, Chk1, by its upstream activator ATR within a multiprotein complex that forms at sites of DNA damage or stalled replication. Claspin is also thought to play an important role in normal replication, and may be a target for certain nongenotoxic stress signalling pathways that inhibit DNA synthesis.